2013
DOI: 10.1111/vop.12109
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar keratoplasty in rabbits using human and rabbit amniotic membrane grafts: a comparative study

Abstract: These differences may reflect a potential reaction to the xenograft. More studies are needed to further characterize these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Corneas harvested on postoperative days 7 and 14 showed inflammatory infiltrates, which were more extensive in the OM-graft group ( Figure 5B). Similar results have been previously reported and suggested an active wound healing (GODOY-ESTEVES et al, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Corneas harvested on postoperative days 7 and 14 showed inflammatory infiltrates, which were more extensive in the OM-graft group ( Figure 5B). Similar results have been previously reported and suggested an active wound healing (GODOY-ESTEVES et al, 2015).…”
Section: Resultssupporting
confidence: 93%
“…Mildto-moderate opacity ( Figure 3B) was observed at all assessments, persisting until day 60 in 33.3% of eyes. Neovascularization was observed after 30 days of assessment (100%); this was likely caused by the xenogenous AM, as noted by GODOY-ESTEVES et al, (2015), who found more inflammatory infiltrates and neovascularization when using human AM than when using allogeneic AM, for lamellar keratoplasty in rabbits. In keeping with the possibility that the neovascularization observed in OM-cell group caused AM, no new vessels were detected in the OM-graft group; however, dehiscence did occur.…”
Section: Resultsmentioning
confidence: 67%
“…In each surgical procedure, the time of the ultrasound (seconds), power of the ultrasound (%), vacuum (mmHg), suction flow (cc/min), amount of BSS, and surgical complications were recorded. Degrees of difficulty with the main incision, auxiliary incision, capsulorhexis, hydrodissection, nucleodissection, phacoemulsification, and deployment of the lens and corneal suture were quantitative and qualitatively assessed according to the Nihill scale – mild, moderate, and severe …”
Section: Methodsmentioning
confidence: 99%